Observational analysis study on the influence of the physical hospital environment on aggressive behaviour and the management thereof in an adult acute psychiatric admission unit - Van den Berg, Marietta (Department of Psychiatry and Mental Health, 2015)
Includes bibliographical references (leaves 81-96).